STRATEGI PENGEMBANGAN TOKO BANGUNAN BERBASIS SWOT DAN FORECASTING PENJUALAN TAHUNAN - Aji, M. Atma; Mahendaringratry, Ayudya (jurnal ATMOSPHERE, 2025)
This study aims to examine the strengths, weaknesses, opportunities, and threats (SWOT analysis) of a building materials store, while also forecasting its future sales performance. To systematically evaluate both internal and external factors, the research applies the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) approaches. The analysis reveals several strengths, such as a wide range of products and a strategic location. However, it also identifies weaknesses, particularly in promotional efforts and inventory management. External factors present both opportunities and challenges — opportunities include ongoing construction projects in the surrounding area and the potential use of social media for marketing. On the other hand, the store faces threats like intense price competition and the growing trend of online shopping. A simple sales forecast was conducted for the upcoming year. The results suggest that without improvements in marketing strategies and operational efficiency, sales are likely to remain stagnant. This is despite the market's potential to grow by up to 20% over the year. Therefore, the study recommends that the store develop more adaptive strategies based on the SWOT analysis and begin leveraging digital media platforms to optimize sales growth.